2010
DOI: 10.1016/j.juro.2010.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Complications After Open Radical Retropubic Prostatectomy Using the Martin Criteria

Abstract: Complications after radical prostatectomy should be reported using a standardized methodology. Using the Clavien-Dindo classification we observed an acceptable overall complication rate. In the majority of cases lower grade complications occurred. Patients of older age, those with greater prostate volume and those who had undergone simultaneous lymphadenectomy were at risk for higher grade complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
5
19
0
2
Order By: Relevance
“…The importance of neurovascular bundle preservation for recovery of potency is well recognized. 32,33 Our neurovascular bundle preservation rate was close to 70%, which is in accordance with many contemporary reported series that have reported rates of 53 to 80%. 32--34 In this study, the rates of nerve preservation were similar in both groups, indicating that it did not have an impact on the postoperative differences observed between them.…”
Section: 15--1729supporting
confidence: 91%
“…The importance of neurovascular bundle preservation for recovery of potency is well recognized. 32,33 Our neurovascular bundle preservation rate was close to 70%, which is in accordance with many contemporary reported series that have reported rates of 53 to 80%. 32--34 In this study, the rates of nerve preservation were similar in both groups, indicating that it did not have an impact on the postoperative differences observed between them.…”
Section: 15--1729supporting
confidence: 91%
“…This finding has been confirmed by other reports. 30 Löppenberg et al 31 reported that the most common complication in their research was anastomotic leakage, which occurred in 424 (14.7%) patients. In our study, 13 (3.4%) cases of anastomotic leakage were reported.…”
Section: Discussionmentioning
confidence: 95%
“…Loeb et al 37 concluded that 96% of patients were dry, which is a satisfactory result regarding urinary continence; no difference was found between patients with T 2 vs. T 3 stage PCa. 31 In a study with a total of 842 cT 3 patients undergoing RP, 79% of cases were dry or used urine pads to prevent incontinence after one year of follow-up. 12 Penson et al…”
Section: Discussionmentioning
confidence: 99%
“…The same classification system has recently been used by urologists to grade postoperative complications following radical prostatectomy, laparoscopic live donor nephrectomy, laparoscopic pyeloplasty, laparoscopic and open partial nephrectomy and most recently Transurethral Resection of Prostate (7,8,9,10). Nephrectomy is the common major surgery in urology; henceforth we retrospectively analyzed our data in all patients who underwent nephrectomy.…”
Section: Introductionmentioning
confidence: 99%